Watch me disappear : a novel - Brown, Janelle (New York : Spiegel & Grau, 2017)
"A beautiful Berkeley mom with a radical past vanishes while hiking, leaving her family to piece together her secrets, in this keenly observed novel for readers of Emma Straub and Maria Semple--from the bestselling author ofAll We Ever Wanted Was Everything"--
"Billie is a beautiful Berkeley mom with a radical past--a teenage runaway from Northern California who took up with a group of environmental activists wanted by the FBI, lived dangerously, but when she meets Jonathan, a tech magazine editor and all around good guy, she settles easily into the life of an eco-conscious, stay-at-home suburban yoga mom. Their daughter Olive, under her mother's watchful gaze, becomes a lovely, introverted, slightly eccentric girl. As she reaches adolescence and needs Billie's full-time attention less, Billie throws herself into extreme sports--marathons, scuba diving, rock climbs, solo hikes. On one of these expeditions, Billie vanishes from the trail--only a hiking boot is found. The family is devastated--a year of intense mourning passes in which they await the closure that a body and a death certificate will bring. Jonathan drinks; Olive grows remote. But then she starts having waking dreams--hallucinations?--in which her very vibrant mother urges the girl to look for her, and Olive begins to believe her mother is still alive and in trouble. Jonathan believes the trauma and anxiety of losing her mother is making Olive ill, until he uncovers a secret that that compels him to consider that Billie may not be dead after all and sends him on his own quest for the truth--about Billie, their marriage, and the things people do in the name of love.."--
Keywords: FICTION / Contemporary Women; FICTION / Family Life; FICTION / Suspense; Domestic fiction; Suspense fiction